Phytotoxins produced by the oak pathogen Discula quercina - Maddau, L.; Perrone, C.; Andolfi, A.; Spanu, E.; Linaldeddu, B. T.; Evidente, A. (Forest Pathology, 2011)
Two phytotoxic metabolites, p-hydroxybenzaldehyde and indol-3-aldehyde, were isolated and identified by spectroscopic methods from solid cultures of Discula quercina, an endophytic fungal pathogen frequently associated with oak decline in Italy. In addition, the fungus produced an unusual acyclic keto acid as a major metabolite, which was identified by spectroscopic and chemical methods as 5-oxo-6E,8E-octadecadienoic acid. In leaf puncture assays on Quercus suber and Q. ilex leaves, indol-3-aldehyde proved to be more toxic than p-hydroxybenzaldehyde, while 5-oxo-6E,8E-octadecadienoic acid was inactive even at the highest concentration used (1 mg ml−1). Although indol-3-aldehyde is a known microbial metabolite, its phytotoxic activity has hitherto not been reported. This report is the first to describe the production of phytotoxic compounds by D. quercina.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Discula quercina (voyant); Oak decline; phytotoxic metabolites